Pendampingan branding identitas usaha upaya peningkatan daya saing UMKM catering “Dapoer Attila” - Adelia, Adelia Rahma Shabira; Widiasmara, Anny (Nur Science Institute, 2023)
Dapoer Attila Catering is one of the MSMEs in Setren Village Bayeman Hamlet Balerejo Madiun Regency. The development of micro, small, and medium enterprises (MSMEs) requires business owners to have a marketing strategy for marketing their products to increase competitiveness and develop their business potential. One of the strategies, in this case, is branding. Branding exists in a product or service, such as a name, sign, symbol, logo, or combination intended to identify a product or service. Branding aims to introduce a product to the broader community, build public trust in a product, and shape public perceptions of the product being sold. Based on the above problems, a community service program was carried out to help brand the identity of the Dapoer Attila Catering business using the Canva application. Based on the service results, the service program has gone well because MSME partners can gain knowledge and skills.